Calculation of Natural and Technological Characteristics of NonNewtonian Oil Reservoirs during their Operation Horizontal Wells - Abbasova, S.V. (Herald of Azerbaijan Engineering Academy, 2024)
Taking into account the affecting factors, such as the initial pressure drop and deformation of the reservoir rocks, in the conditions of a deep occurrence of a non-Newtonian oil field, a method for determining the change in time of the natural and technological characteristics averaged over the reservoir - reservoir pressure and reservoir porosity, as well as well flow rate is proposed. Thus, by determining the changes in time of the average values of reservoir pressure and reservoir porosity, the well productivity is determined for a given allowable drawdown on the reservoir, as an integral characteristic of well operation. Calculations were carried out at different values of rock compressibility, and for these values the indicators of changes in reservoir pressure and horizontal well production were determined.